TOLERANSI MENURUT PERSPEKTIF STUDI ISLAM: PEMAHAMAN, RELEVANSI, TANTANGAN DAN PROSPEK DALAM MASYARAKAT KONTEMPORER - Heni Suryani; Kambali (CV. Adiba Aisha Amira, 2023)
The study on the concept of tolerance in the context of Islamic studies emphasizes the importance of respecting differences and diversity within society. Islamic teachings highlight the values of tolerance derived from the Qur'an and the Hadith of the Prophet Muhammad, but its practical implementation often faces challenges, including internal and external conflicts as well as difficulties in appreciating differences of opinions. These challenges become significant obstacles to achieving authentic tolerance. The relevance of tolerance values is crucial in building a multicultural society where tolerance plays a vital role as the foundation for social harmony in an environment filled with cultural, religious, and belief diversity.The application of tolerance values enables individuals from diverse backgrounds to respect, accept, and appreciate differences, paving the way for better understanding, reducing conflicts, and establishing a solid foundation for cooperation and harmony in a multicultural society. Despite the acknowledgment of the concept of tolerance in Islamic teachings from the Qur'an and the Hadith of the Prophet Muhammad, practical challenges such as conflicts, stereotypes, prejudices, and differing views on religious pluralism pose significant barriers.However, with an inclusive approach, deep understanding, and appropriate education, tolerance values in Islam can be implemented more effectively, opening the path for more efficient practices of tolerance concepts in Islamic studies. This, in turn, can result in better harmony and cohesion among communities.